EFEK BUMERANG NEGATIF PESAN PERSUASIF KAMPANYE VAKSIN ‘’MEASLES-RUBELLA’’ OLEH KEMENTERIAN KESEHATAN REPUBLIK INDONESIA - ANDHIKA KURNIAWAN PONTOH; FARRAH MARDIATI SOEHARNO; MUTIA ADIA RISIAD (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
Persuasive messages in public health campaigns are aimed at influencing public attitudes and behaviors on health consequences. The operational formula for creating persuasive messages is health vulnerability multiplied by severity, using a logic of losses/disadvantages in order to motivate the public to change their behavior for healthy living. This paper intends to analyze the persuasive message of the MR vaccine campaign and see the response that occurred in the community towards the campaign. This paper tries to examine the process of social judgment among the communities that results in a response of rejection and a boomerang effect on the campaign. This paper concludes that the negative boomerang effect on the MR Vaccine campaign carried out by the Indonesian Ministry of Health is largely due to the ego involvement of key figures or opinion leaders that influence the perceptions and behavior of the audience who receives and processes the message. Opinion leaders in this case are religious institutions such as MUI who published findings on MR vaccine substance. The boomerang effect that occurs is the contrast attitude and behavior of the campaign audience whose values/principles anchors hit oppose and far from the content of the MR Vaccine campaign message.